Temporary disengagement and re-engagement in human immunodeficiency virus care in a rural county serving pastoralist communities in Kenya: a retrospective cohort study. Issue 2 (22nd June 2019) - Yonga, Paul; Kalya, Stephen; Lynen, Lutgarde; Decroo, Tom
Abstract: Background: Pastoralist communities are known to be hard to reach. The magnitude of temporary disengagement from human immunodeficiency virus (HIV) care is understudied. Methods: We conducted a retrospective cohort study of temporary disengagement (2 weeks late for a next appointment), virologic response, lost to follow-up (6 months late) and re-engagement in care among patients who started antiretroviral therapy between 2014 and 2016 in Baringo County, Kenya. Predictors of re-engagement after disengagement were estimated using logistic regression. Results: Of 342 patients, 76.9% disengaged at least once (range 0–7). Of 218 patients with a viral load (VL), 78.0% had a suppressed VL. Those with a history of temporary disengagement from care were less likely to suppress their VL (p=0.002). Six patients had treatment failure (two consecutive VLs >1000 copies/mm 3 ) and all had disengaged at least once. After disengagement from care, male patients (adjusted odds ratio [aOR] 0.3 [95% confidence interval CI 0.2 to 0.6]; p<0.001) and patients with World Health Organization stage III–IV (aOR 0.3 [95% CI 0.1 to 0.5; p<0.001) were less likely to re-engage in care. Conclusions: Temporary disengagement was frequent in this pastoralist setting. This indicator is often overlooked, as most studies only report binary outcomes, such as retention in care. Innovative strategies are required to achieve HIV control in rural settings like this pastoralist setting.